2011
DOI: 10.1016/j.eurpsy.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the social network, stigma and empowerment on the quality of life in patients with schizophrenia

Abstract: Following a recovery approach in mental health services by focusing on the improvement of the social network, stigma reduction and especially on the development of personal strength has the potential to reduce depression in patients with psychosis and improving their QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
98
2
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(147 citation statements)
references
References 41 publications
(53 reference statements)
28
98
2
12
Order By: Relevance
“…It has been well documented that people with mental health problems report high levels of discrimination (Sibitz et al 2011;Evans-Lacko et al 2012;Farrelly et al 2014;Griffiths et al 2014). There is an increasing effort to try to end discrimination towards people affected by mental health problems (Heinz et al 2015;Mehta et al 2015;Thornicroft et al 2015;Wahlbeck, 2015;Weissman, 2015), with the promotion of antistigma programmes worldwide such as 'Like Minds, Like Mine' (Vaughan & Hansen, 2004;Thornicroft et al 2014), 'Opening Minds' (Sartorius, 2014;Stuart et al 2014), and 'Open the Doors' (Rüsch et al 2005;Gaebel et al 2008;NHS Scotland, 2008;Thornicroft et al 2008;Evans-Lacko et al 2012;Evans-Lacko et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that people with mental health problems report high levels of discrimination (Sibitz et al 2011;Evans-Lacko et al 2012;Farrelly et al 2014;Griffiths et al 2014). There is an increasing effort to try to end discrimination towards people affected by mental health problems (Heinz et al 2015;Mehta et al 2015;Thornicroft et al 2015;Wahlbeck, 2015;Weissman, 2015), with the promotion of antistigma programmes worldwide such as 'Like Minds, Like Mine' (Vaughan & Hansen, 2004;Thornicroft et al 2014), 'Opening Minds' (Sartorius, 2014;Stuart et al 2014), and 'Open the Doors' (Rüsch et al 2005;Gaebel et al 2008;NHS Scotland, 2008;Thornicroft et al 2008;Evans-Lacko et al 2012;Evans-Lacko et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Path analysis results found that the recovery program improved patients' social networks, enhanced empowerment and reduced stigma. This recovery program also reduced depression in patients with psychosis and improved their QOL [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, before starting to implement methods of improving social network and social support, the efficacy of such interventions requires further investigation [21,22].…”
Section: A Theoretical Framework About Autonomy As a Capacitymentioning
confidence: 99%